Model Understanding By Design (UBD) untuk Pembelajaran Matematika yang Adaptif dan Inklusif di Sekolah - Wiratomo, Yogi; Wiratomo, Yulan Mailani; Wiratomo, Ersita Afiyah Utami; Wiratomo, Endang Sekar Ayu; Wiratomo, Shinta Irabyatul Rahman (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
The implementation of the Understanding by Design (UbD) model in mathematics instruction aims to establish a planning framework focused on conceptual understanding and knowledge transfer. By integrating differentiated instruction and Universal Design for Learning (UDL) principles, UbD provides a systematic foundation for designing adaptive and inclusive learning experiences. Through a literature review of relevant theories and educational practices, a conceptual framework is developed to support responsiveness to the diverse needs, learning styles, and characteristics of students. Findings indicate that the integration of UbD with adaptive and inclusive strategies enhances student engagement, accessibility, and learning outcomes in mathematics. This approach is relevant for fostering equitable, meaningful, and contextual learning across educational levels. Keywords : Understanding by Design, adaptive learning, inclusive education, mathematics instruction